Understanding Financial Management Practices in Sociological Perspectives: A Transcendental Phenomenological Study - La ode sumail; Salma Abdullah; Hisnol Jamali (Publication Division of International Ecsis Association, 2022)
The purpose of this study is to uncover financial management practices from a sociological perspective. Conventional finance focuses only on materials or assets, which seem to have no spirit or social oxygen, even though those spirits have an important role in financial governance. This study used transcendental phenomenological methodology. A total of five key informants were involved in the study. All the key informants involved have at least ten years of experience as banana traders